An Analysis of the Factors Influencing Tax Avoidance With Corporate Governance as A Moderating Variable - Gamal Ali Akbar Hasibuan; Iskandar Muda; Narumondang Bulan Siregar (Harmoni Economics: International Journal of Economics and Accounting, 2025)
This research explores the key factors influencing tax avoidance, with a particular focus on the influence of corporate governance as a moderating factor among manufacturing firms registered on the Indonesia Stock Exchange between 2020 and 2024. Data for the analysis were sourced directly from the official publications of the exchange, and the strategy for drawing the research sample applied was purposive sampling. Out of a total population of 228 listed manufacturing firms during the study period, 65 companies were selected as the final sample. The study utilized secondary data and employed panel data regression analysis combined with Moderated Regression Analysis (MRA), processed using EViews 12 software.The results demonstrate that profitability, leverage, inventory intensity, and sales growth each have a positive and statistically significant relationship with tax avoidance. On the contrary, firm size does not exhibit a significant effect. Additionally, corporate governance—represented by the proportion of independent commissioners—significantly moderates the effect of profitability, leverage, inventory intensity, and sales growth on tax avoidance by amplifying these relationships. In contrast, its moderating influence on firm size tends to weaken the relationship with tax avoidance.